Behuria mestrealvarensis (Melastomataceae): a new species on an inselberg in Espírito Santo, Brazil - Iglesias, Diego Tavares; Dutra, Valquíria Ferreira; Goldenberg, Renato (Phytotaxa, 2016)
Behuria mestrealvarensis (Melastomataceae) from the state of Espírito Santo, Brazil, is described, illustrated and compared with B. capixaba, the species most similar to it. Behuria mestrealvarensis differs from B. capixaba by the glabrous petioles and hypanthia, by the solitary flowers or these in simple or compound triads up to 7 flowers, elliptic bracteoles almost the same size of the pedicel and hypanthium, sepals with eciliate margins and ovary apex with trichomes up to 0.5 mm. It occurs in a single locality, on an isolated, ca. 800m elev. inselberg. Due to its restricted occupancy area, fragmented landscape and poor habitat quality, this species must be considered as Critically Endangered according to IUCN criteria.